Impact of HIV Infection and Zidovudine Therapy on RBC Parameters and Urine Methylmalonic Acid Levels - Adediran, Adewumi; Osunkalu, Vincent; Wakama, Tamunomieibi; John-Olabode, Sarah; Akinbami, Akinsegun; Uche, Ebele; Akanmu, Sulaimon (Interdisciplinary Perspectives on Infectious Diseases, 2016)
Background. Anaemia is a common complication of human immunodeficiency virus (HIV) infection. The aim of this study was to investigate the impact of HIV infection and zidovudine on red blood cells (RBC) parameters and urine methylmalonic acid (UMMA) levels in patients with HIV infection. Material and Methods. A cross-sectional study involving 114 subjects, 94 of which are HIV-infected nonanaemic and 20 HIV negative subjects (Cg) as control. Full blood count parameters and urine methylmalonic acid (UMMA) level of each subject were determined. Associations were determined by Chi-square test and logistic regression statistics where appropriate. Results. Subjects on zidovudine-based ART had mean MCV (93 fL) higher than that of control group (82.9 fL) and ART-naïve (85.9 fL) subjects and the highest mean RDW. Mean UMMA level, which reflects vitamin B12 level status, was high in all HIV-infected groups but was significantly higher in ART-naïve subjects than in ART-experienced subjects. Conclusion. Although non-zidovudine therapy may be associated with macrocytosis (MCV > 95 fL), zidovudine therapy and ART naivety may not. Suboptimal level of vitamin B12 as measured by high UMMA though highest in ART-naïve subjects was common in all HIV-infected subjects.